Determinants of the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange - Fuad Fuad; Imamudin Yuliadi (Journal of Economics Research and Social Sciences, 2021)
The stock market is one of the essential components of Indonesia's economy. As the market's improvement is quite acceptable nowadays, some macro variables affect stock price volatility. Therefore, research on the determinant of the Indonesian composite index is required. This study aims to determine the effect of world oil prices and macroeconomic variables on the Composite Stock Price Index. The variables used in this study are inflation, exchange rates, interest rates, and world oil prices. This study uses secondary data and time series from January 2015 to December 2019 to obtain 60 monthly data. The method used to examine the data is the Partial Adjustment Model (PAM) method using Eviews 7 and performs assumption tests. Based on the analysis that has been carried out, the study results found that the inflation and exchange rate variables have a negative and significant effect on the Indonesian Composite Stock Price Index. The interest rate and world oil price variables positively and significantly affect the Indonesian Composite Stock Price Index